Pengaruh Penggunaan Akun Instagram @ussfeeds Terhadap Pemenuhan Kebutuhan Informasi Followers Dikalangan Mahasiswa Fakultas Ilmu Sosial Jurusan Ilmu Komunikasi Universitas Islam Negeri Sumatera Utara - Erizal, Nurfan; Kholil, Syukur; Yasmin, Nabila (Universitas Labuhanbatu, 2024)
Instagram is currently one of the media most frequently used by students at the Faculty of Social Sciences, Department of Communication Sciences, North Sumatra State Islamic University to search for information. This research aims to find out how much influence the use of the Instagram account @ussfeeds has on fulfilling the information needs of followers among students at the Faculty of Social Sciences, Department of Communication, North Sumatra State Islamic University. The theory used in this research is the Uses and Gratifications theory, new media and fulfilling information needs. This research uses a quantitative approach with data collection techniques in the form of distributing questionnaires or questionnaires which are measured using a Likert scale, then processed and then concluded. This research used purposive sampling, with the Slovin formula with an error rate of 10%, and the total sample in this research was 78 respondents. The analysis method is in the form of validity testing, reliability testing, and hypothesis testing using the Spearman's Rho Rank-Order Correlation formula via SPSS version 29 and using the Guilford scale or correlation coefficient. The results of this research show that Ha is accepted and Ho is rejected, indicated by a significant value = <0.001, which means a significant number <0.05, which means there is a significant relationship between variable x and variable y. This means that there is an influence between the use of the @ussfeeds Instagram account on fulfilling the information needs of followers among students at the Faculty of Social Sciences, Department of Communication Sciences, North Sumatra State Islamic University.On the Guilford scale the result (rho) = 0.666 means this valueis on a scale (0.41 – 0.70), then this shows that there is a significant relationship between variable x and variable y. The value of the coefficient of determination (r2) obtained a figure of 0.666, which meansshows that variable.